2018
DOI: 10.1111/ijpo.12271
|View full text |Cite
|
Sign up to set email alerts
|

The positive association of infant weight gain with adulthood body mass index has strengthened over time in the Fels Longitudinal Study

Abstract: The infant weight gain-adulthood BMI association was over two times stronger among a cohort born during the obesity epidemic era compared with cohorts born earlier in the 20th century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“… Rapid weight gain during early childhood may lead to excess adiposity, and metabolic syndrome later in life, especially in countries undergoing a rapid nutrition transition. [77][78][79][80]  Intake over several months may affect recipients gut microbiome and may also influence their taste preferences and later life consumption patterns. 80,81  Potential mis-targeting of supplements due to errors in the detection of MAM or SAM children, or sharing with siblings, may lead to excess energy intakes among children who are not energy deficient or suffering from acute malnutrition.…”
Section: Health Platformsmentioning
confidence: 99%
“… Rapid weight gain during early childhood may lead to excess adiposity, and metabolic syndrome later in life, especially in countries undergoing a rapid nutrition transition. [77][78][79][80]  Intake over several months may affect recipients gut microbiome and may also influence their taste preferences and later life consumption patterns. 80,81  Potential mis-targeting of supplements due to errors in the detection of MAM or SAM children, or sharing with siblings, may lead to excess energy intakes among children who are not energy deficient or suffering from acute malnutrition.…”
Section: Health Platformsmentioning
confidence: 99%
“…Law et al [ 60 ] found that systolic blood pressure increased for each decrease in birth weight standard deviation score and for each increase in early weight gain standard deviation score. The interaction is complex with evidence from the Fels Longitudinal Study showing that a higher increase in weight-for-length z score in the first 2 years of life was associated with higher adulthood BMI and systolic blood pressure with the strongest effect in the most recent cohort during the obesity epidemic [ 61 ]. This brings into question environmental or food quality factors potentially mediating some of these effects.…”
Section: Neonatal Risk Factors For Later Development Of Cardiovascula...mentioning
confidence: 99%
“…The interaction is complex with evidence from the Fels Longitudinal Study showing that a higher increase in weightforlength z score in the first 2 years of life was associated with higher adulthood BMI and systolic blood pressure with the strongest effect in the most recent cohort during the obesity epidemic. 61) This brings into question environmental or food quality factors potentially mediating some of these effects. Yet even in adults, a systematic review has shown that rapid growth in those born SGA may be associated with higher blood pressure, higher BMI and more insulin resistance but is also associated with better cognition at 17-26 years of age.…”
Section: Cardiovascular Disease Risk In Adulthoodmentioning
confidence: 99%
“…Overweight and obesity in children under 5 years of age, defined respectively as two and three standard deviations above the World Health Organization weight-for-height growth standard median [ 8 ], affected an estimated 38.2 million children in 2019 [ 8 ]. Longitudinal data show that the trajectory of infant weight gain increases the risk of obesity in childhood and adulthood [ 9 , 10 ]. Obesity during childhood increases the risk of chronic disease, such as type 2 diabetes, cardiovascular disease and non-alcoholic fatty liver disease [ 11 ]; children with obesity are over five times more likely to have obesity into adulthood [ 12 ].…”
Section: Introductionmentioning
confidence: 99%